Video games, crime and next-gen deviance: reorienting the debate - Kelly, Craig; Lynes, Adam; Hoffin, Kevin (Emerald Publishing, 2020)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. In recent decades the video games industry has grown astronomically, quickly becoming a substantial part of our everyday lives. Alongside the rise of this technology, the media, academia and, in some cases, governments, have drawn correlations between video games and serious instances of violence, focusing most notably on mass shootings. This narrow debate has distracted from our understanding of many of the harms which video games can, in some cases, cause, perpetuate or hide. Drawing upon the emerging deviant leisure perspective, this book seeks to re-orientate the debate on video games and their associated potential harms. Through the examination of culturally embedded harms such as gambling, sexual violence and addiction, together with the rise in swatting and other activities, the authors explore the notion that video games are inexplicably intertwined with aspects of deviancy